Circular agriculture: Integrating microalgae in poultry effluent treatment and sunflower (Helianthus annuus L.) crop development: CIRCULAR AGRICULTURE: INTEGRATING MICROALGAE IN SUNFLOWER CROP DEVELOPMENT - N GANDHI; Y RAMA GOVINDA REDDY; CH VIJAYA (Journal of Oilseeds Research, 2025)
The discharge of untreated wastewater from chicken processing industries posessignificant environmental and agricultural challenges due to its high organic load and pollutant content. Thisstudyevaluatesthe physico-chemical properties of wastewater generated from a chicken processing unit and its suitability for reuse after phycoremediation using indigenous microalgae.Thewastewater analysisrevealed high total dissolved solids(TDS) (20 ppt), biochemical oxygen demand (BOD5) (980 mg/L), chemical oxygen demand (COD) (1030 mg/L), turbidity (380 NTU), and elevated levels of oil, grease (280 mg/L), and protein (158 mg/L). Heavymetal analysis confirmed negligible levels of lead (Pb) and chromium(Cr), with no detectable mercury (Hg), cadmium (Cd), or arsenic (As). The wastewater was brownish-red and emitted a strong odor, indicating significant organic contamination. Phycoremediation, an eco-friendly and sustainable wastewater treatment approach, was applied using indigenous microalgae screened frompaddyfields. Over a 10-daytreatment period, BOD and COD levelssignificantlyreduced to 52 mg/L and 160 mg/L, respectively. Electrical conductivity (EC) decreased from 20 mS/cm to 5 mS/cm, and nutrient concentrations, including phosphorus and total nitrogen, declined, highlighting the effective pollutant removal bymicroalgae. The treated wastewater (TCW) met WHO-recommended standards, making it suitable for agricultural reuse. To assess its agricultural applicability, sunflower was cultivated using TCW, borewell water (control), untreated wastewater (CW), and a 1:1 mixture of control water and CW. Germination rates, growth parameters, and physiological responses were analyzed. Sunflowers irrigated with TCW exhibited improved germination (88%), germination index (11.8), and mean germination rate (0.286), while CW-treated seeds showed the lowest germination (65%). Growth analysis over 90 days demonstrated enhanced relative growth rate, net assimilation rate, and leaf area duration under TCW irrigation. Additionally, agronomic performance, including crop growth rate, productivity, and relative production efficiency, was significantly higher with TCW compared toCW. Post-cultivation soil analysisrevealed that CWirrigation increased salinity, raised soil pH (8.1), and caused excessive nitrate nitrogen (40 mg/100g) and phosphorus(65 mg/100g) accumulation. In contrast, TCW maintained soil properties closer to control conditions, preventing degradation. Statistical analysis confirmed significant improvements in soil health with TCW,supporting itsfeasibilityas an alternative irrigation source. These findings highlight the potential of phycoremediated wastewater for sustainable irrigation, mitigating environmental pollution while enhancing agricultural productivity.